Proximal gastric vagotomy, fundoplication, and lesser-curve necrosis. Issue 6176 (2nd June 1979) - Kennedy, T; Magill, P; Johnston, G W; Parks, T G
Abstract : Out of 400 patients who underwent proximal gastric vagotomy (PGV), three developed lesser-curve necrosis (LCN) leading to perforation within the first seven days. In each case diagnosis was delayed but the patient survived after a second operation. In each an associated Nissen fundoplication had been carried out; we used the combined operation in only 33 patients. Delayed LCN occurred in a patient who had undergone splenectomy at the time of the PGV and in a fifth patient treated elsewhere who had also undergone fundoplication. These findings indicate that early postoperative gastric distension with gas, not readily voided after fundoplication, may aggravate local vascular factors and predispose to LCN. We suggest that PGV combined with fundoplication may be dangerous.